Anal mucosectomy for haemorrhoids: should we start to speak Chinese?. (27th March 2013) - Dindo, D.; Hahnloser, D.
Abstract: Aim: Circular stapled mucosectomy is the standard therapy for the treatment of symptomatic third‐degree haemorrhoids and mucosal prolapse. Recently, new staplers made in China have entered the market offering an alternative to the PPH stapling devices. The aim of this prospective randomized study was to compare the safety and efficacy of these new devices. Methods: Fifty patients with symptomatic third‐degree haemorrhoids were randomized to mucosectomy either by using stapler A (CPH32; Frankenman International Ltd, Hong Kong, China; n  =   25) or stapler B (PPH03; Ethicon Endo‐Surgery, Spreitenbach, Switzerland; n  =   25). All procedures were performed by two experienced surgeons. After the stapler was fired by one surgeon, the other surgeon, who was blinded for stapler type, evaluated the stapler line. Postoperative outcome including pain, complications and patient satisfaction were analysed. Results: Demographic and clinical features were no different between the groups. There was no significant difference regarding venous bleeding ( P  =   0.55), but arterial bleeding was significantly more frequent when stapler B was used ( P  <   0.001). This led to significantly more suture ligations ( P  =   0.002). However, no differences regarding operation time ( P  =   0.99), weight of the resected mucosa ( P  =   0.81) and height of the stapler line (anterior, P  =   0.18; posterior, P  =   0.65) were detected. Postoperative pain scores (visual analogue scale) and patient satisfaction were no different either ( P  =   0.91 and P  =   0.78, respectively). No recurrence or incontinence occurred during follow‐up. Conclusions: CPH32 required significantly fewer sutures for bleeding control along the stapler line after circular mucosectomy. However, operation time, rate of postoperative complications and patient satisfaction were similar in both groups.